Early Childhood Education and Development: Exploring Effective Approaches to Early Learning - Ahmad Shofi Mubarok (Education Studies and Teaching Journal (EDUTECH), 2024)
Early Childhood Education (PAUD) is a critical stage that contributes significantly to children's holistic development, including cognitive, social, emotional and physical aspects. This research aims to explore the role of collaboration between parents and teachers in improving early childhood learning outcomes in urban and rural environments, as well as identifying effective strategies for overcoming educational gaps in both contexts. The research method used is a systematic literature review with the PRISMA approach, which ensures the validity and reliability of the findings. The research results show that effective collaboration between parents and teachers and the application of child development theory can create a holistic and supportive learning environment. The implication of this research is the need for PAUD programs that emphasize strong collaboration between educators and parents, as well as policies that support better resource allocation for rural areas.